Faunistic analysis of mosquitoes (Diptera, Culicidae) in Teruel Province (Northeastern Spain) - Rubén Bueno Marí (Global Journal of Zoology - Peertechz Publications, 2017)
Intensive samplings for mosquito larvae were conducted between June and October 2014 in the main representative wetlands of the Teruel province (Northeastern Spain). All water bodies listed in the Inventory of Protected Wetlands from Aragón belonging to the study area, as well as also other fl uvial environments, fountains, ponds, streams and reservoirs that had optimal conditions for the development of these dipterans were visited. A total of 2.329 mosquito larval exemplars belonging to 18 species were collected. It is important to note that 4 of these species (Anopheles plumbeus, Ochlerotatus geniculatus, Culex laticinctus and Culex mimeticus) are fi rst recorded in the study area. The main bio ecological aspects of recorded species and the epidemiological interest of those mosquitoes are briefl y discussed in the text.